The Pressure Drop for Laminar Flow in 3D Straight and Elbow Pipes Using Computational Fluid Dynamics - Iwan Kurniawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2023)
Designing piping systems for laminar flow requires an understanding of pressure drop. Pressure drop can offer insights for selecting pipe materials, designing an efficient piping system, and choosing the appropriate elbows and fittings. Utilizing numerical simulations, the pressure drop in straight pipes, 45o bends, 90o bends, and 180o bends is examined. Velocity profiles for straight pipes and bends are compared, revealing the increase in pressure drop caused by the bend in comparison to the straight pipe. The numerical simulation results indicate that the bend results in an increased pressure drop in the pipe's flow.